2009
DOI: 10.1353/arw.0.0135
|View full text |Cite
|
Sign up to set email alerts
|

Hunger, Healing, and Citizenship in Central Tanzania

Abstract: Abstract:This article draws on newspaper commentary, Nyaturu hunger lore, and ethnographic research to describe how central Tanzanian villagers accessed food aid from the state during the East African food crisis of 2006. Through leveraging their political support and their participation in national development agendas, rural inhabitants claimed their rights. Yet it was through these exchanges that the state converted food aid into political power. The article argues that the highly ritualized gift of food aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…Specifically, I have shown that the contemporary political idiom of paternity organizes and legitimates the political structure in four main ways. First, through its assertions of direct descent from the Nyerere line, CCM proclaims itself the sole heir and executor of Nyerere's political estate, which was secured through his legitimacy as “one who did not fill his own belly.” This association complicates and contradicts a reality in which Tanzanians perceive their current leaders to be eating national resources (Phillips 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, I have shown that the contemporary political idiom of paternity organizes and legitimates the political structure in four main ways. First, through its assertions of direct descent from the Nyerere line, CCM proclaims itself the sole heir and executor of Nyerere's political estate, which was secured through his legitimacy as “one who did not fill his own belly.” This association complicates and contradicts a reality in which Tanzanians perceive their current leaders to be eating national resources (Phillips 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Singida elders defended their continued support of the ruling party (and justified their own claims to authority) with protests, “What, and refuse the hand of the father who has fed us? It is not possible.” And, as I have shown elsewhere, even villagers themselves made use of this paternalistic state discourse to lay claim on food aid and other development resources (Phillips 2009). This latter appropriation of paternal imagery is also captured by a newspaper cartoonist: a villager calls out “Daddy!” to former President Mkapa, who holds the reward of a primary school (drawn as a chicken bone) just out of reach of the citizens (Mpangala 2008).…”
Section: Kikwete Comes To Singidamentioning
confidence: 98%
“…And in this context of recurrent drought and food crisis, where the work of food production relies on a short rainy season between December and March, the stakes of such labour are also very high. Singida is one of the more food-insecure regions in Tanzania (Phillips 2009), but is not exceptional in the pervasiveness of hunger or in the degree of its seriousness. 2 A brief sketch of the productive efforts of three diverse but interconnected households in rural Singida reveals the energies that people eke, recycle, metabolize and repurpose to drive their everyday lives betwixt and between national energy infrastructures.…”
Section: The Metabolics Of Everyday Life In Three Singida Householdsmentioning
confidence: 99%
“…Of relevance to this thesis there were some studies that identified some potential negative effects of EFA on socio-cultural practices and socioecological relations within Indigenous cultures in Africa (e.g., Bersaglio et al 2015, Phillips 2009, Reidy 2012 and PNG (Mogina 2000). However, these critical studies were more common in the 1970s and 1980s (e.g., Cuny 1979, Maxwell and Singer 1979, Sinclair and Fryxell 1985, Waddel 1974).…”
Section: Overview Of the Emergency Food Aid Literaturementioning
confidence: 99%
“…Despite the suggested improvements to the effectiveness of EFA (e.g., Gilligan andHoddinott 2007, Omamo et al 2010), there has been less progress on finding consensus regarding the often-reported, yet argued to be empirically elusive (Barrett and Maxwell 2005), negative societal effects of EFA (e.g., Bakhit and Hayati 1995, Bersaglio et al 2015, Clay 1987, Cuny 1979, Fletcher 1991, Jaspars 2018, Phillips 2009, Reidy 2012, Sinclair and Fryxell 1985, Waddell 1975. Distilling evidence from these studies reveals a compelling case for the persistent misunderstanding of the underlying vulnerability by humanitarian agencies and donors through only providing short-term relief while not addressing, and likely reinforcing, the accrued vulnerability that led to the disaster (see specifically Mustafa 2003, Sinclair andFryxell 1985).…”
Section: Gaps Identified In the Emergency Food Aid Literaturementioning
confidence: 99%